Value addition of low fat chicken sausage with rice and wheat flour (Bangladesh Journal of Animal Science, 2020)
The study was conducted to evaluate the effect of rice and wheat flours on low fat chicken sausages. Sausages were prepared into three different groups: control; broiler breast meat sausage without any flour (T1), sausage with addition of 10% rice flour (T2) &10% wheat flour (T3). All parameters were analyzed at 0, 15th and 30th days of storage period. The proximate compositions of different sausages were analyzed and highly significant (p